Development of a Komagataella phaffii cell factory for sustainable production of ( +)-valencene - Jintao Cheng; Jiali Chen; Dingfeng Chen; Baoxian Li; Chaozhi Wei; Tao Liu; Xiao Wang; Zhengshun Wen; Yuanxiang Jin; Chenfan Sun; Guiling Yang (Microbial Cell Factories)
Abstract Background Sesquiterpene ( +)-valencene is a characteristic aroma component from sweet orange fruit, which has a variety of biological activities and is widely used in industrial manufacturing of food, beverage and cosmetics industries. However, at present, the content in plant sources is low, and its yield and quality would be influenced by weather and land, which limit the supply of ( +)-valencene. The rapid development of synthetic biology has accelerated the construction of microbial cell factories and provided an effective alternative method for the production of natural products. Results In this study, we first introduced the ( +)-valencene synthase into Komagataella phaffii by CRISPR/Cas9 system, and successfully constructed a ( +)-valencene producer with the initial yield of 2.1 mg/L. Subsequently, the ( +)-valencene yield was increased to 8.2 mg/L by fusing farnesyl pyrophosphate synthase with ( +)-valencene synthase using the selected ligation linker. High expression of key genes IDI1, tHMG1, ERG12 and ERG19 enhanced metabolic flux of MVA pathway, and the yield of ( +)-valencene was further increased by 27%. Besides, in-situ deletion of the promoter of ERG9 increased the yield of ( +)-valencene to 48.1 mg/L. Finally, we optimized the copy number of farnesyl pyrophosphate synthase and ( +)-valencene synthase fusion protein, and when the copy number reached three, the yield of ( +)-valencene achieved 173.6 mg/L in shake flask level, which was 82-fold higher than that of the starting strain CaVAL1. Conclusions The results obtained here suggest that K. phaffii has the potential to efficiently synthesize other terpenoids.